Legal Consequences of Debtor Bankruptcy on Recipient Agreements Made Prior to Bankruptcy Based on Law Number 37 of 2004 - Laia, Felix Otaris; Martono Anggustin; Roida Nababan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study explores the legal consequences of bankruptcy on reciprocal agreements made prior to the debtor’s declaration of bankruptcy, as governed by Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. In the event of bankruptcy, control and management of the debtor's assets are transferred to a curator, which can alter the implementation of reciprocal agreements that have not been fully or partially fulfilled. According to Article 36 of Law No. 37/2004, parties who have agreements with the debtor can request confirmation regarding the continuation of the agreement from the curator within a specified period. If the curator decides not to continue, the agreement is terminated, and the other party has the right to claim compensation and will be recognized as a concurrent creditor. This study also examines the legal protection available to the parties involved, as well as the practical implications for legal and business relationships after a bankruptcy decision is made. The findings demonstrate that bankruptcy significantly affects the performance of reciprocal agreements, necessitating adjustments to the rights and obligations of all parties based on the provisions of the Bankruptcy Law. These adjustments are essential to ensuring justice and legal certainty for all parties involved in such agreements, balancing the interests of creditors, debtors, and other stakeholders. Ultimately, the study emphasizes the importance of understanding the legal framework surrounding bankruptcy and its consequences on ongoing contractual relationships, as well as the need for a fair and transparent process in dealing with claims and obligations post-bankruptcy.